Regional Differences of the Impact of Healthy Aging on Myeloarchitecture at 7T. (20th December 2022) - Mueller, Susanne G
Abstract: Background: Cortical gray matter (cGM) loss in healthy aging has been well documented by volumetric MRI. Less well known though is if this age‐related cGM loss is layer‐specific or diffuse. Benefiting from the higher resolution at 7T and the close relationship between cortical cyto‐ and myeloarchitecture (1) this project used a newly developed technique for the differentiation between heavily (layers IV‐VI) and sparsely (layers I‐III) myelinated cortical layers to investigate this question. Method: The 7T MP2Rage images (TR/TE/TI1/TI2=5000/2.45/900/2750 ms, 0.7x0.7x0.7mm) of 45 healthy controls (age: 19‐75, f/m=23/22) from the ATAG data repository (http://doi.org/10.5061/dryad.fb41s ) were used for this project and the following contrasts generated: 1. T1 weighted image (UNI). 2. T1 relaxation image (T1map). 3. Inv1/Inv2 ratio map (In1/In2 ratio). After skull‐stripping and intensity calibration a fourth contrast (UNI/T1map ratio) was calculated. The UNI was segmented in SPM and a binary cortical rim mask calculated. With these four contrasts as input K‐means clustering was used to identify 6 clusters within this mask: CSF cluster, CSF/cGM transition cluster, WM cluster, WM/cGM transition cluster, heavily myelinated cGM cluster (hcGM) and sparsely myelinated cGM cluster (scGM) (Figure 1). The hGM and scGM maps were warped into a common space with SPM's DARTEL. SPM was used to compare hcGM and scGM differences of young adults (n=27, 19‐27 years) with that of older adults (n=18, 42‐75 years). Result: Figure 2 shows that hcGM loss was restricted to the mid‐posterior cingulate and parahippocampal gyrus. Age‐related scGM loss was more diffuse and affected mesial prefrontal, opercular cortex and superior temporal gyrus. Conclusion: Age related cGM loss affects sparsely and heavily myelinated layers differently. The heavily myelinated posterior cingulate belongs to the late myelinating structures. The hcGM loss there is consistent with the "last in, first out" hypothesis. The scGM loss in the mesial prefrontal, opercular, superior temporal region affects sparsely myelinated layers I‐III that are known to have a high synaptic density (1) indicating that it is probably mostly driven by dendritic loss. Although preliminary, the data presented here indicate that this new technique might provide a better insight into the nature of GM loss in healthy and abnormal aging. 1. Neuroimage 2019;197:716‐741